Jane's fighting ships, 2006-2007 - Saunders, Stephen (Jane's Information Group, 2006)
A reference to the changing capabilities of modern navies and coast guards, their ships and maritime aircraft in service and under construction. It includes inventories for 164 navies around the world with details of displacement and dimensions, main machinery, speed and range, weapons systems and sensors, and operational status